Introduction to CMOS VLSI design - Roy Chowdhury,S (Everest Publishing House, 2010)
Introduction to CMOS VLSI design / Roy Chowdhury,S.. -- Kolkata: Everest Publishing House, 2010 621.395 R888 No. of Copies : 3